The foreshore zone determination according to the Greek legislation, using geologic and océanographie data - Pehlivanoglou, K. G.; Martsoukou, M. (Bulletin of the Geological Society of Greece, 2007)
The available scientific field data of the marine and the coastal enviroment, (the wind and the wave field data, the shallow area bathymetry, the coastal area geomorphology and topography, etc.), joint to deep and shallow wave prediction numerical modelling (by means of the wind and bathymetry measurements), calculation of the near shore wave height and maximum wave run up, were used to support the mapping of the innermost limit of the foreshore zone, according to the Greek legislation which defines that "the foreshore is the zone of land wetted by the highest however unexceptional sea wave run up " and the Supreme Administrative Court standard case law. These methods applied for two areas, which completely differ for the wind and the wave field, the géomorphologie and topographic characteristics of the coastal area, proposing different procedures for the determination of the innermost limit of the foreshore zone. The proposed limits of the foreshore zones for both areas, resulted from the study, are compared to the limits proposed by the authorised Administrative Commissions, which were published in the Official Gazette and also were applied by the local authorities for the coastal area management